2005
DOI: 10.1093/jee/98.5.1654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GF-120 Fruit Fly Bait Concentrations on Attraction, Feeding, Mortality, and Control of Rhagoletis indifferens (Diptera: Tephritidae)

Abstract: Effects of different concentrations of GF-120 NF Naturalyte Fruit Fly Bait on attraction and feeding responses, mortality, and control of the western cherry fruit fly, Rhagoletis indifferens Curran, were determined. In the laboratory, flies that had been exposed to sugar and yeast extract and then deprived of all food for 16-20 h were attracted to 40.0% GF-120, but not to 0.6 and 4.8% GF-120 (vol:vol). Nonstarved flies were not attracted to any concentration. Flies in the field were not attracted to 55.6% GF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Roots of D. elliptica contain many compounds, such as rotenoids, isoflavones, ceramides and rotenoids (Wu et al, 2012). LC 50 values reported in this work are higher compared to values reported from other studies (see Mangan, 2009;McQuate et al, 2005;Wang et al, 2013;Yee and Chapman, 2013;Zhang et al, 2015). The concentration and dose of toxicants used to kill 50% of a population of fruit flies are variable depending on species and insecticidal compound.…”
Section: Discussionmentioning
confidence: 51%
“…Roots of D. elliptica contain many compounds, such as rotenoids, isoflavones, ceramides and rotenoids (Wu et al, 2012). LC 50 values reported in this work are higher compared to values reported from other studies (see Mangan, 2009;McQuate et al, 2005;Wang et al, 2013;Yee and Chapman, 2013;Zhang et al, 2015). The concentration and dose of toxicants used to kill 50% of a population of fruit flies are variable depending on species and insecticidal compound.…”
Section: Discussionmentioning
confidence: 51%
“…However, it is important to note that the attractiveness of the bait under Þeld conditions may be compromised over time, although some studies have demonstrated that attractants currently in the mix may remain active for at least 24 h (Mangan 2009). However, Yee and Chapman (2005) suggested that the suppression of ßy populations is primarily because of the attraction of ßies to the bait.…”
Section: Discussionmentioning
confidence: 99%
“…For R. mendax Curran, the exposure to 40 ppm spinosad resulted in mortality higher than 80% (Barry and Polavarapu 2005). An LC 50 of 0.7 ppm was reported for R. indifferens (Yee and Chapman 2005), whereas for B. dorsalis and B. cucurbitae the LC 50 was 5.5 and 3.3 ppm, respectively (Stark et al 2004). In this study, fresh 24 concentration of 24 ppm resulted in a mortality of at least 90% for A. obliqua and A. serpentina, while for A. ludens the lowest mortality obtained was 63%.…”
Section: Discussionmentioning
confidence: 99%
“…1099, effective 30 September 1968 (Smith and Kupferman 2003). Since about 2005 (Yee and Chapman 2005;Warner 2008), the fly has been managed in Washington [which produces 55% of fresh market cherries in the U.S. (Smith and Kupferman 2003)] and other cherry-producing areas using mostly spinosad bait sprays (GF-120 Ò NF Naturalyte Ò , Dow AgroSciences, Indianapolis, IN) rather than cover sprays. Spinosad bait is applied weekly, or reapplied after rainfall, to kill flies before they are able to lay eggs in fruit, which first occurs when flies are *7 days old (Frick et al 1954).…”
Section: Introductionmentioning
confidence: 99%